PENGEMBANGAN E-MODUL AJAR PADA CAPAIAN PEMBELAJARAN PROFESI DAN KEWIRAUSAHAAN DIBIDANG INDUSTRI KECANTIKAN DAN SPA FASE E SMK NEGERI 1 LAMONGAN - Irma Nur Fitriya; Novia Restu Windayani; Nia Kusstianti; Biyan Yesi Wilujeng (Program Studi Pendidikan Tata Rias, 2025)
This research aims to develop an E-module for Professional and Entrepreneurship learning in the Beauty and SPA Industry in the Basics of Beauty subject which is implemented at SMK Negeri 1 Lamongan. This research model uses the ADDIE method. This type of research uses